Counseling on the Use of Meta Ai in Improving Digital Literacy in Rural Communities in Indonesia: Pengabdian - Made Susilawati; Fadil Mas’ud; Luluk Sarifah; Rinovian Rais; Johannes P Kumagaya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service was conducted in several villages in Indonesia, including Legian Badung, Baubau Kupang, and Ogan Jaya in North Lampung, over periods ranging from two weeks to one month. The aim was to provide counseling on the use of Meta AI to improve digital literacy in rural communities in Indonesia. The methodology involved discussions with colleagues and village officials to identify suitable themes, followed by obtaining permission from village authorities. The implementation stage included counseling on how to use Meta AI, covering aspects like opening WhatsApp, accessing Meta AI through the chat tab, agreeing to terms, typing prompts, sending messages, and providing feedback. The counseling also highlighted the advantages of Meta AI, such as its ease of use, multi-language capabilities, and 24-hour availability. The authors found that Meta AI's simple interface allows users of varying technological backgrounds to interact with it easily, and its constant availability and multi-language support enhance its utility as an educational and communication tool globally.